Evaluating the Impact of the Medication Therapy Management Program on Patients’ Blood Pressure and Obesity: A Pre-Post Study - Hossein Zare; Augustine C. Amuta; Magaly Rodriguez de Bittner; Sade Osotimehin; Laurine Thomas; Twarnisha M. Stokes; Amber Allen; Jacob Riley; Caitlin L. Murphy; Debra M. Collier; Roland J. Thorpe; Michelle Spencer; et al. (Journal of Primary Care & Community Health)
Background: Hypertension and obesity are major public health problems in the United States and Maryland. Objectives: To assess the impact of Medication Therapy Management (MTM) on controlling hypertension and obesity in a sample in Southern Maryland: Prince George’s, Calvert, Charles, and St. Mary’s counties. Methods: 171 patients with high blood pressure were enrolled in an MTM program for 12 months. Patients received at least one pharmacist consultation between September 2021 and September 2023. We employed a pre-post prospective study design to assess the impact of MTM on patients’ blood pressure management. We examined the association between MTM and systolic blood pressure (SBP) and diastolic BP (DBP) as the primary outcome, and weight and body mass index (BMI) as secondary outcomes. We used descriptive analysis and fixed effect regression models to present the association between outcome variables and enrollment time in the program. Results: Our findings showed that the MTM reduced uncontrolled hypertension by 17.5 percentage points, weight by 3.6lbs (10.2), and BMI by 0.6 kg/m 2 (2.1). The regression model showed that the MTM intervention reduced the prevalence of uncontrolled hypertension (−1.81, CI: [−3.11, −0.51]), and obesity (BMI > 30, −1.85 (CI: [−3.12, −0.57]), by 12 months of enrolling in the program. During this time SBP reduced to −10.37 mmHg (CI: [−19.62, 1.2]). Conclusions: Our results suggest that policymakers should prioritize promoting MTM services as an effective means of blood pressure control. Combining a community health worker (CHW) model with community-based pharmacists can further improve health outcomes for patients with hypertension.